2022
DOI: 10.3390/molecules27030700
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Postmortem Ethanol Production/Insights into the Origin of Higher Alcohols

Abstract: The forensic toxicologist is challenged to provide scientific evidence to distinguish the source of ethanol (antemortem ingestion or microbial production) determined in the postmortem blood and to properly interpret the relevant blood alcohol concentration (BAC) results, in regard to ethanol levels at death and subsequent behavioral impairment of the person at the time of death. Higher alcohols (1-propanol, 1-butanol, isobutanol, 2-methyl-1-butanol (isoamyl-alcohol), and 3-methyl-2-butanol (amyl-alcohol)) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Interestingly, the non-production of 1-propanol and 1-butanol in certain microbial culture sets highlights the variability and selective nature of microbial congener alcohol synthesis, corroborating reports of their absence in postmortem cases where ethanol production was detected [18,26,[37][38][39]. This variability reinforces the argument for considering the five higher alcohols (isobutanol, 2-methyl-1-butanol / amyl alcohol and 3-methyl-1-butanol / isoamyl alcohol, 1-butanol and 1-propanol) as critical biomarkers for microbial ethanol synthesis [26], advising against their use as internal standards in forensic laboratories during ethanol analysis due to potential postmortem microbial production.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Interestingly, the non-production of 1-propanol and 1-butanol in certain microbial culture sets highlights the variability and selective nature of microbial congener alcohol synthesis, corroborating reports of their absence in postmortem cases where ethanol production was detected [18,26,[37][38][39]. This variability reinforces the argument for considering the five higher alcohols (isobutanol, 2-methyl-1-butanol / amyl alcohol and 3-methyl-1-butanol / isoamyl alcohol, 1-butanol and 1-propanol) as critical biomarkers for microbial ethanol synthesis [26], advising against their use as internal standards in forensic laboratories during ethanol analysis due to potential postmortem microbial production.…”
Section: Discussionsupporting
confidence: 75%
“…Regarding autopsy bloods, the EC models showed the best applicability among the bacterial and yeast models, and especially in cases with BAC ranging from 0.5 to 1.0 g/L (57-64% of samples for EC5-6 and almost 40% of samples for EC1-4) and in cases with putrefaction (20-50% of putrefactive cases) (Figure 1). These findings in autopsy bloods, when compared with the previous results on the applicability of the clostridial models that were reported to apply successfully in up to 95% of autopsy cases with obvious signs of putrefaction and up to 85% of cases with BAC < 0.7 g/L [26,28], showed that the EC models followed the clostridial ones in applicability. The fungal models were by far the least applicable of all; possibly, they can be applicable in specific cases with elevated glucose levels.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Several authors correlate an increase in the alcohol concentration with post-mortem production due to the action of different species of bacteria. In most of the cases in which the production of post-mortem ethanol was observed, the concentration was not higher than 0.3 g/L [29][30][31][32]. In Table 2, the analyte concentrations found in peripheral blood and urine are reported.…”
Section: Resultsmentioning
confidence: 99%
“…When putrefaction occurs, higher alcohols are also often produced, such as the propanols, butanols, and amyl alcohols (Boumba, 2022). These may be detected in a gas chromatographic analysis for ethanol, although their presence will be dependent on the organisms present and the degree of putrefaction providing the method is capable of detecting these higher alcohols.…”
Section: Alcoholmentioning
confidence: 99%